Analisis QoS (Quality of Service) Pada Jaringan Internet (Studi Kasus: Universitas Advent Indonesia) - Elmor Benedict Wagiu; Abraham Butar-butar; Jay Idoan Sihotang (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2019)
The connectivity of the internet network is something that cannot be separated from the daily activities at present. The speed of data transfer and the quality of service becomes a benchmark for its assessment. Universitas Advent Indonesia is an educational institution that provides internet access to all campus residents as a means for students to search for data and information. The bandwidth allocated for students is 60 Mbps, while 40 Mbps is allocated for office buildings and lecturer housing which are also within the campus area. This study uses bandwidth, throughput, delay, jitter, and packet loss parameters using Iperf, Ping, and Command Prompt software to find out the Quality of Service from an internet connection on campus. The research aims to 1) determine the performance of internet network services and 2) provide results of measurements of the analysis of Quality of Service at Universitas Advent Indonesia. The research methodology used for this study is to use literature studies and direct research in several strategic locations. The conclusions of this study are: 1) the performance of the internet network in the NACB area, male dormitory and female dormitory is very good with an index value of 4 based on the calculation of QoS parameters, namely bandwidth, delay, jitter, throughput and packet loss. 2) the quality of internet client network services has met the standardization value according to the TIPHON version. The average value of client bandwidth capacity obtained from NACB is data transfer speed of 6.48 Mbps. The average value of the client bandwidth capacity of the male dormitory is 13.2 Mbps. While the average value of client bandwidth capacity in female dormitories is 10.1 Mbps. Keywords: quality of service, internet, bandwidth, throughput, delay, jitter, packet loss